(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In this scientific article, while objectively analyzing the development of criminal law in the path of independent development that has taken the Republic of Uzbekistan today, we have witnessed that during the past period, crimes are developing as society progresses and appear in new forms every day. we can be It is explained in a short article that the crime of "arbitrariness", which is considered a crime against the administrative order, also needs a deep study, and how important the object is in its qualification. Information is also given about the impact of crime on our sovereignty.